Fruits Quality and Sensory Analysis - Paola Sánchez-Bravo; Luis Noguera-Artiaga (Horticulturae)
With the objective of using sensory analysis tools to dually consider the changes in quality that fruit undergoes (functional, nutritional, and sensory) throughout its growth, processing, and shelf life and consumer acceptance, given consumers are increasingly demanding sustainable and higher-quality food, we edited this Special Issue on “Fruits Quality and Sensory Analysis” (URL: https://www [...]